VD_FINDINFO Décision / 2011 / 362 vom 23. Juni 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, PROLONGATION, RISQUE DE FUITE, PROPORTIONNALITÉ | 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)